Assessing Rigid and Non-Rigid Spatial Thinking. (May 2022) - Maheshwary, K.; Eisenbart, B.; Zorn, S.; Nelius, T.; Gericke, K.; Matthiesen, S.; Blessing, L.
Abstract: Spatial Thinking (ST) is an important part of reasoning. In contrast to Rigid ST (R-ST), Non-Rigid ST (NR-ST) has hardly been researched and tests do not exist, even though NR-ST is crucial for professions that deal with space and time such as engineering and design. Our study at 4 different universities confirms that R-ST does not predict performance in NR-ST; that performance in Non-Rigid ST is significantly lower than in R-ST; and that performance of students in later semesters is not better than in the first semesters. These results highlight the need for further research into NR-ST.